(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2018)
The analysis focuses on how the precept was conceived in the discussion of the Constitution and how it has come to be applied in October 2017, with concrete measures that the Senate has approved by an absolute majority and that have essentially consisted of cease all the members of the Government of Catalonia, being substituted by the Government of the State, and with early dissolution of the Regional Parliament and convocation of Autonomous Elections.